Sistem Pakar Untuk Diagnosa Penyakit Kehamilan Menggunakan Metode Dempster-Shafer Dan Decision Tree - minardi, joko popo (JSINBIS (Jurnal Sistem Informasi Bisnis), 2013)
Dempster-Shafer theory is a mathematical theory of evidence based on belief functions and plausible reasoning, which is used to combine separate pieces of information. Dempster-Shafer theory an alternative to traditional probabilistic theory for the mathematical representation of uncertainty. In the diagnosis of diseases of pregnancy information obtained from the patient sometimes incomplete, with Dempster-Shafer method and expert system rules can be a combination of symptoms that are not complete to get an appropriate diagnosis while the decision tree is used as a decision support tool reference tracking of disease symptoms This Research aims to develop an expert system that can perform a diagnosis of pregnancy using Dempster Shafer method, which can produce a trust value to a disease diagnosis. Based on the results of diagnostic testing Dempster-Shafer method and expert systems, the resulting accuracy of 76%. Â  Keywords: Expert system; Diseases of pregnancy; Dempster Shafer